Efeito ansiolítico e antidepressivo do desidrodieugenol (Bis-eugenol) em camundongos : estudo neurocomportamental e neuroquímico - Amaral, Jeferson Falcão do (2010)
Desidrodieugenol, known as bis-eugenol, is an ortho dimer that of similarly to eugenol was able to exhibits anti-inflammatory and antioxidant. Bis-eugenol has also showed antidepressant effect, however, the biological actions of bis-eugenol on experimental models for screening of antidepressant activity are still unknown. The present study investigated the possible antidepressant-like activity of bis-eugenol in the forced swimming test (FST) and the tail suspension test (TST) in mice and the involvement of monoaminergic system in this effect. In addiction, the neurochemical analysis on brain monoamines of mice acutely treated with bis-eugenol was also conducted. Besides, the central effects of bis-eugenol were evaluated, also, animal models of anxiety such as barbiturate-induced sleeping time, hole board, elevated plus maze, pentilenotetrazole induced-convulsions and white/black test. Bis-eugenol drecreased the immobility time in the FST which accompanying changes in ambulation in the open-field test at 10 mg/kg, i.p., nevertheless, it induced ambulation at 25 and 50 mg/kg doses. The higher anti-immobility effect of bis-eugenol (50 mg/kg, i.p.,) was prevented by pre-treatment of mice with PCPA 100 mg/kg, i.p., ( inhibitor of serotonin synthesis, 4 consecutive days), prazozin (1 mg/kg, i.p., α1-adrenoceptor antagonist), yohimbine (1 mg/kg, i.p., α2-adrenoceptor antagonist), SCH23390 (15 µg/kg, s.c., D1 receptor antagonist) or sulpiride (50 mg/kg, i.p., D2 receptor antagonist). Bis-eugenol showed anxiolytic activity in the hole board, elevated plus maze and white/black test and it seems there no performance of bis-eugenol on the gabaergic system, once flumazenil no reverted the anxiolytic effect of bis-eugenol in the plus maze test. Monoamines analysis using High Performace Liquid Chromatograph (HPLC) reveled a significant increase in 5-HT, NE, DA levels in brain striatum, as well as the metabolites DOPAC, HVA and 5-HIAA were also increased. The present study suggests that the anti-immobility or antidepressant-like effect of bis-eugenol in the FST is related to the monoaminergic system, likely due to increase of brain monoamines. An anxiolytic effects was observed which no related of the gabaergic system, once flumazenil no reversed the anxiety effects of the bis-eugenol in the plus maze test.